PENINGKATAN PROFESIONALISME GURU MELALUI SUPERVISI KLINIS DENGAN PENDEKATAN LESSON STUDY DI MADRASAH TSANAWIYAH BANTUL KOTA (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
This study aims to improve the professionalism of teachers through methods of lesson study. School action research was conducted three cycles, each cycle consisting of three rounds with the stage of plan, do, and see / reflection. Implementation of clinical supervision with lesson study approach as a learning improvement efforts have shown excellent results. It can be seen in which (1) the students' motivation increases and the classroom atmosphere more conducive so that students can be comfortable in learning, (2) the learning process, the students dared to express / ask questions (visits and discussions and presentations) and the absorption of students to the subject matter increases, (3) the disclosure of the teachers, classrooms are used not closed so that other teachers can see what is done in the learning process are implemented, (4) the motivation of teachers, the teachers are motivated to seek and explore various methods or learning strategies, ( 5) teachers learn from each other and cooperate in improving the quality of the learning process, and (6) the teacher got a lot of enlightenment, apart from peers, as well as from the facilitators that almost every encounter is always present to provide support, both when performing plan (plan), do (execution / implementation), and see (reflection).